Rural development: research priorities. - North Central Regional Center for Rural Development; North Central Regional Center for Rural Development; Farm Foundation (Chicago, Ill.) (Ames, Iowa State University Press, 1973)
"A collection of papers presented during a symposium (Developing research priorities on the problems of rural development) Zion, Illinois, May 9-11, 1972; sponsored by the North Central Regional Center for Rural Development, the North Central Regional Research Strategy Committee on Rural Community and Resource Development, and the Farm Foundation."
Includes bibliographical references.
lje 24/1/18
Loans
Keywords: Rural development